Improved Relapse-Free Survival in Patients With High Natural Killer Cell Doses in Grafts and During Early Immune Reconstitution After Allogeneic Stem Cell Transplantation - Minculescu, Lia; Fischer-Nielsen, Anne; Haastrup, Eva; Ryder, Lars Peter; Andersen, Niels Smedegaard; Schjoedt, Ida; Friis, Lone Smidstrup; Kornblit, Brian Thomas; Petersen, Søren Lykke; Sengelov, Henrik; Marquart, Hanne Vibeke (Frontiers in Immunology, 2020)
Mature immunocompetent cells from the stem cell graft as well as early robust immune reconstitution are essential for the graft-versus-tumor (GVT) effect to eliminate residual malignant cells after allogeneic hematopoietic stem cell transplantation (HSCT). In this prospective study we characterized graft composition of T- and NK cell subsets in 88 recipients of peripheral blood stem cell grafts with multicolor flowcytometry. Our primary aim was to analyze the impact of graft composition on immune reconstitution and clinical outcomes after transplantation. Patients transplanted with graft NK cell doses above the median value of 27x106/kg had significantly increased relapse-free-survival compared to patients transplanted with lower doses, HR 2.12, (95% CI 1.01-4.45, p=0.04) Peripheral blood concentrations of NK cells obtained from donors before G-CSF mobilization were significantly correlated to graft NK cell doses (Spearman’s ρ 0.53, p=0.03). The dose of transplanted NK cells/kg correlated significantly with NK cell concentrations in patients early after transplantation (Spearman’s ρ 0.26, p=0.02, and ρ=0.35, p=0.001 for days 28 and 56, respectively). Early immune reconstitution above median values of NK cells was significantly associated with improved relapse-free survival (HR 2.84 [95%CI 1.29-6.28], p=0.01, and HR 4.19[95% CI 1.68-10.4], p=0.002, for day 28 and 56, respectively). Early concentrations above the median value of the mature effector CD56dim NK cell subset were significantly associated with decreased relapse incidences at 1 year, 7 % (95% CI 1.8-17) versus 28 % (95% CI 15-42), p=0.04, and 7 % (95% CI 1.8-18) versus 26 % (95% CI 14-40) %, p=0.03, for days 28 and 56, respectively. The results suggest a protective effect of high doses of NK cells in grafts and during early immune reconstitution and support the perception of NK cells as innate effector cells with anti-tumor effects in the setting of allogeneic stem cell transplantation.